06_ - M.H. Abenova,; R.S. Parmanova,; K.O. Bolshekbayeva, (Academic Journal of Physical and Chemical Sciences, 2019)
At present, with the transition of the economy to market relations, the independence of enterprises, their economic and legal responsibility is increasing. Dramatically increases the value of financial stability of business entities. Business leaders are faced with the problems of financial management. Understanding that the company needs to change the management system, reduce costs, more effectively manage financial resources comes quickly. The question is how to do this? How to calculate the true cost of products, how to plan purchases with existing stocks, in the improvement of which processes in the first place you need to invest. The efficiency of using financial resources is characterized by asset turnover and profitability indicators. Therefore, management efficiency can be increased by reducing the turnover period and increasing profitability by reducing costs and increasing revenue.